Evaluación antibacteriana de extracto y aceite esencial de Pumamaqui (Oreopanax ecuadorensis Seeman) FRENTE A: ( Staphylococcus aureus ATCC: 25923, Streptococcus pyogenes ATCC: 19615, Streptococcus pneumoniae ATCC: 49619 y Streptococcus mutans ATCC: 25175), patógenos de enfermedades respiratorias - González Sánchez, Andrés Rafael (2016)
The main objective of this project work is to evaluate the antibacterial activity of the essential oil and fluid extract of Oreopanax ecuadorensis Seeman. It was used the essential oil of the vegetal specie obtained by duct diffusion and they were performed dilutions of the same with DMSO, working with the next concentrations (5%, 2.5% and 1.25%), also was evaluated the activity of the fluid extract at 25% of concentration performed by percolation. The duct diffusion technique was made with different concentration levels of essential oil and only one concentration of fluid extract compared to: Staphylococcus aureus ATCC: 25923, Streptococcus mutans ATCC: 25175, Streptococcus pneumoniae ATCC: 49619 y Streptococcus pyogenes ATCC: 19615, those bacteria considered as representative as principal pathogens of respiratory diseases. Based on the results and the statistical analysis it could be concluded that Oreopanax ecuadorensis Seeman, with the 25% of concentration by the extract presented inhibitory activity in front of Streptococcus pyogenes ATCC 19615 with 12.1 mm, follow of Streptococcus mutans ATCC 25175 with 10.9 mm and 10.4 mm to Streptococcus pneumoniae ATCC 49619, while not evidenced inhibitory activity in front of Staphylococcus aureus ATCC 25923. Whereas the essential oil presents in the 5%, 2.5% and 1.25% concentrations values of 6 mm of diameter of inhibition to: Staphylococcus aureus ATCC 25923, Streptococcus mutans ATCC 25175, Streptococcus pneumoniae ATCC 49619, and y Streptococcus pyogenes ATCC 19615.